Factors affecting the knowledge and practices of BEC members towards birth control method in Barangay Guihaman, Leganes, Iloilo. - Castano, Jude Mae B.
This paper examined the factors affecting the knowledge and practices about reproductive health, family planning, and birth control methods of Basic Ecclesial Community (BEC) members in Barangay Guihaman, Leganes, Iloilo. The study probed the source of knowledge and the amount of knowledge BEC members have, as guage of the influence of the Roman Catholic Church and the strategies used by the Roman Catholic Church in persuading BEC members to adopt its ethical stance. The differentiated understanding of male and female BEC members regarding gender roles and its effect on decisions pertaining to the type of birth control method used is analyzed.